2013
DOI: 10.1111/ger.12035
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of three antimicrobial mouthrinses on the disinfection of toothbrushes stored in closed containers: a randomized clinical investigation by DNA Checkerboard and Culture

Abstract: Culture and DNA Checkerboard showed positive signals of bacterial contamination. Mouthrinses that contains 0.12% of chlorhexidine gluconate were more effective in reducing bacterial colonisation on the toothbrushes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
10
0
4
Order By: Relevance
“…The use of a toothbrush cap has also been reported to increase bacterial survival on toothbrushes. 2,5,18 Nascimento et al 19 investigated the effectiveness of three antimicrobial mouth rinses for toothbrush disinfection under in vivo conditions. The participants of that study stored their toothbrushes in closed containers to avoid external contamination.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a toothbrush cap has also been reported to increase bacterial survival on toothbrushes. 2,5,18 Nascimento et al 19 investigated the effectiveness of three antimicrobial mouth rinses for toothbrush disinfection under in vivo conditions. The participants of that study stored their toothbrushes in closed containers to avoid external contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Nascimento et al (2014) in their study found that 8 h immersion in Periogard solution was highly effective against bacterial toothbrush contamination. According to their study we can determine that Periogard in spray form was considered more economical than 8 h immersion in Periogard solution with the same efficacy.…”
Section: Discussionmentioning
confidence: 98%
“…Future studies should assess the localization of the biofilm, and the effect of specific cleaning procedures to reduce or prevent biofilm build-up, as the currently recommended approach to empty and carefully swab the container with a clean paper tissue after each use is inefficient. For example, specific cleaning procedures (e.g., simple immersion in 0.12% chlorhexidine gluconate or 1% sodium hypochlorite for 20 h) have been described to reduce successfully the bacterial load on toothbrushes (Balappanavar et al, 2009;do Nascimento et al, 2014;Mehta et al, 2007;Nelson-Filho et al, 2000, 2006. Furthermore, the possible impact of using SAF with a mouth-rinse instead of water on the bacterial colonization of the nozzle and/or the device should be assessed, as the manufacturer in fact recommends using the SAF with tap water or with a mouth-rinse.…”
Section: Discussionmentioning
confidence: 99%